Ethnicity-Specific Skeletal Muscle Transcriptional Signatures and Their Relevance to Insulin Resistance in Singapore - Tan, Amelia Li Min; Langley, Sarah R; Tan, Chee Fan; Chai, Jin Fang; Khoo, Chin Meng; Leow, Melvin Khee-Shing; Khoo, Eric Yin Hao; Moreno-Moral, Aida; Pravenec, Michal; Rotival, Maxime; Sadananthan, Suresh Anand; Velan, S Sendhil; et al. (The Journal of clinical endocrinology and metabolism, 2019)
CONTEXT: Insulin resistance (IR) and obesity differ among ethnic groups in Singapore, with the Malays more obese yet less IR than Asian-Indians. However, the molecular basis underlying these differences is not clear. OBJECTIVE: As the skeletal muscle (SM) is metabolically relevant to IR, we investigated molecular pathways in SM that are associated with ethnic differences in IR, obesity, and related traits. DESIGN, SETTING, AND MAIN OUTCOME MEASURES: We integrated transcriptomic, genomic, and phenotypic analyses in 156 healthy subjects representing three major ethnicities in the Singapore Adult Metabolism Study. PATIENTS: This study contains Chinese (n = 63), Malay (n = 51), and Asian-Indian (n = 42) men, aged 21 to 40 years, without systemic diseases. RESULTS: We found remarkable diversity in the SM transcriptome among the three ethnicities, with >8000 differentially expressed genes (40% of all genes expressed in SM). Comparison with blood transcriptome from a separate Singaporean cohort showed that >95% of SM expression differences among ethnicities were unique to SM. We identified a network of 46 genes that were specifically downregulated in Malays, suggesting dysregulation of components of cellular respiration in SM of Malay individuals. We also report 28 differentially expressed gene clusters, four of which were also enriched for genes that were found in genome-wide association studies of metabolic traits and disease and correlated with variation in IR, obesity, and related traits. CONCLUSION: We identified extensive gene-expression changes in SM among the three Singaporean ethnicities and report specific genes and molecular pathways that might underpin and explain the differences in IR among these ethnic groups.
Keywords: index tělesné hmotnosti; signální transdukce; Ethnicity; Gene Expression Profiling; celogenomová asociační studie; Cohort Studies; transkriptom; mužské pohlaví; Signal Transduction; Muscle, Skeletal; Singapore; Adult; mladý dospělý; kohortové studie; Body Mass Index; Singapur; Transcriptome; Young Adult; Humans; kosterní svaly; etnicita; stanovení celkové genové exprese; dospělí; inzulinová rezistence; Insulin Resistance; Genome-Wide Association Study; lidé; Male